Does Financial Liberalization Lead to Poverty Alleviation? New Evidence from Nigeria (2020)
The study examined anew the empirical question of whether financial liberalization induces poverty alleviation. There is a theoretical expectation that liberalizing the financial market will lead to greater savings mobilization, greater access to credit facilities and poverty alleviation. Using a time-series data spanning 38 years (1980-2018), the study analyzed the effect of financial liberalization on credit availability to the private sector, the manufacturing sector especially the small & medium enterprises and the agricultural sector in Nigeria. The Bounds testing approach to co-integration employed within the framework of Autoregressive Distributed Lag model (ARDL) was used to generate the coefficients. The coefficient of financial liberalization-though positive in all the parameter estimates, it is not significant. This led us to the conclusion that despite the advantages of financial liberalization, its benefits are yet to bring about significant positive increases or changes in the volume of credit to the private sector and in poverty alleviation. Inferring upon this, we deduced that the continued liberalization of the financial system though indicating a positive long run impact on financial widening (or financial deepening as the case may be), its manifestation on quantum of credit to the private sector and on poverty alleviation is yet to be realized in Nigeria. The study recommended, amongst others, that government should re-think and re-tool the process in ways that will generate stability in the financial system and unleash the potentials of the process to generate greater savings and ultimately greater investment in the real sectors of the economy.